Magnetohydrodynamics flow and thermal behavior of nanofluid between two parallel walls with thermal radiation and joule heating applications - Abbas, Tasawar; Mumtaz, Faisal; Khan, Sami Ullah (Multiscale and Multidisciplinary Modeling, Experiments and Design, 2025)
This investigation aims to present an unsteady magnetohydrodynamics (MHD) flow and thermal behavior of a hybrid nanofluid (HNF) confined between two parallel walls. The heat transfer is subject to thermal radiation and Joule heating applications. Three various types of nanoparticles are used because of their unique thermal characteristics. The investigation is impacted with Joule heating and heat dissipation applications. Additionally, we carried out the effects of shapes of three different types of nanoparticles ( A l 2 O 3 , C u , C u O ) and the developed mathematical model is based on the hybrid nanofluid’s thermal characteristics and related principles.The existence of Joule heating and thermal radiation has a major impact on heat transport, resulting in a 27.6% increase in fluid temperature with rising radiation parameter values. A dimensionless system has been developed for modeled problem with help of appropriate variables. The well-known shooting with RK technique is used to obtain the required solution. The flow parameters include the variations in the heat transportation and thermo-physical characteristics of used nanoparticles. The integration of time-dependent consequences, which have been completely disregarded in previous investigations, is a significant novelty of current model. The results show that raising the magnetic field intensity reduces fluid velocity while increases heat transfer via the Lorentz force. Furthermore, thermal radiation has been shown to have a major influence on temperature distribution, with Joule heating increasing thermal energy generation inside the fluid. This study sheds new light on transient thermal transport in hybrid nanofluids, with potential applications in industrial cooling, thermal energy storage, and biomedical engineering. According to obtained results, increase in the amount of copper oxide nanoparticles enhances the temperature profile. The applied magnetic field generates a Lorentz force ( M = 0.8 ) , resulting in a 14.2% drop in velocity profile. Furthermore, entropy production analysis shows a 22.3% increase in irreversibility with increasing magnetic field strength and Eckert number.